Mortality from Heart Failure in Brazil: An epidemiological analysis (2014–2024) (Research, Society and Development, 2025)
Heart failure (HF) remains one of the leading causes of hospitalization and in-hospital mortality in Brazil, particularly in contexts of socioeconomic inequality. The main objective of this study was to analyze socioeconomic, age-related, and geographic disparities, as well as temporal trends in hospitalization and mortality rates from heart failure in Brazil (2010–2023), estimating the preventive effect of antihypertensive pharmacological coverage through multilevel panel models (Poisson/NegBin) with offset = log(population). In parallel, an integrative review (PubMed, Embase, Cochrane, Web of Science, and SciELO, 2010–2025) was conducted, including clinical trials, cohorts, and meta-analyses on antihypertensive classes and blood pressure targets related to reducing mortality or hospitalizations from HF. Results showed an average national increase of 1.9% per year in in-hospital lethality, more pronounced in the South region (+3.0%/year) and among older adults aged 60–79 years (≈2.1%/year). Men and women presented similar growth (+2.0%/year), while Black, Brown, and White groups ranged between 2.2% and 2.3%/year; the Indigenous population remained stable. It is concluded that, although HF hospitalizations have decreased, in-hospital lethality continues to expand heterogeneously across the territory. In this scenario, health policies that expand primary care coverage regionally, ensure equitable access to evidence-based therapies, and reinforce blood pressure control are necessary to transform pharmacological advances into tangible gains in survival and equity.